Non-contrast MRI of Inner Ear Detected Differences of Endolymphatic Drainage System Between Vestibular Migraine and Unilateral Ménière's Disease - Leng, Yangming; Lei, Ping; Chen, Cen; Liu, Yingzhao; Xia, Kaijun; Liu, Bo (Frontiers in Neurology, 2022)
Objective: We aimed to evaluate the diagnostic performance of some anatomical variables with regard to endolymphatic sac (ES) and duct (ED), measured by non-contrast three-dimensional sampling perfection with application optimized contrasts using different flip angle evolutions (3D-SPACE) magnetic resonance imaging (MRI), in differentiating vestibular migraine (VM) from unilateral Ménière's disease (MD). Methods: Eighty-one patients with VM, 97 patients with unilateral MD, and 50 control subjects were enrolled. The MRI-visualized parameters, including the distance between the vertical part of the posterior semicircular canal and the posterior fossa (MRI-PP distance) and visibility of vestibular aqueduct (MRI-VA), were measured bilaterally. The diagnostic value of the MRI-PP distance and MRI-VA visibility for differentiating VM from unilateral MD was examined. Results: (1) Compared with the VM patients, patients with unilateral MD exhibited shorter MRI-PP distance and poorer MRI-VA visibility. No differences of the MRI-PP distance and MRI-VA visibility were detected between VM patients and control subjects. (2) No significant interaural difference of the MRI-PP distance and MRI-VA visibility was observed in patients with VM and those with unilateral MD, respectively. (3) Area under the curve (AUC) showed a low diagnostic value for the MRI-PP distance and MRI-VA visibility, respectively, in differentiating between the VM and unilateral MD. Conclusions: Based on non-enhanced MRI-visualized measurement, anatomical variables with regard to endolymphatic drainage system differed significantly between the patients with VM and those with unilateral MD. Further investigations are needed to improve the diagnostic value of these indices in differentiating VM from unilateral MD.